Prevalence of frailty syndrome and related factors in older adults living in a nursing home - Semsinnur Gocer (Medicine Science, 2019)
In this study, it was aimed to determine prevalence of frailty syndrome in older adults living in a nursing home in Kayseri and to assess relationship of frailty with sociodemographic characteristics and health-related conditions. This cross-sectional study was conducted on older adults living in a nursing home in Kayseri in 2016. Data were collected by using a sociodemographic questionnaire, Katz Index of Independence of Daily Living Activities, Instrumental Activities of Daily Living Scale, Geriatric Depression Scale and Study of Osteoporotic Fracture Index. It was aimed to include 128 older adults living in the nursing home. A total of 105 people were included. Chi-square test was used for statistical analysis. Of subjects, 56.2% were men; 5.7% were married and 45.7% were literate, 92.4% had health insurance, and 70.5% had regular income. Mean age was 77.5±8.7 years. Prevalence rate of frailty syndrome was 31.4%. Prevalence rate was found to be higher in women and in those aged ≥85 years. It was found that walking difficulty and walking stick use were more prevalent, while general health perception and sleep quality were poorer in older adults with frailty syndrome. Frailty syndrome was detected in approximately one-third of the study group. Prevalence rate of frailty syndrome was found to be higher among women and it was found to be increased by advancing age. The frailty has negative influence on health perception, sleep quality and walking difficulty. It is important to assess older adults for frailty and risk factors and to raise awareness the caregivers on frailty syndrome.. [Med-Science 2019; 8(1.000): 21-6]